Răspuns:
Explicație pas cu pas:
a = -9/4
b = 7/6
c = 13/12
(a + b) + c = (-9/4 + 7/6) + 13/12 = (-27/12 + 14/12) + 13/12 = -13/12 + 13/12 = 0
a + (b + c) = -9/4 + (7/6 + 13/12) = -9/4 + (14/12 + 13/12) = -9/4 + 27/12 = -9/4 + 9/4 = 0
_______________
a = -1 + 1/2 = -2/2 + 1/2 = -1/2
b = -2 + 2/3 = -6/3 + 2/3 = -4/3
c = -3 + 3/4 = -12/4 + 3/4 = -9/4
(a + b) + c = (-1/2 - 4/3) - 9/4 = (-3/6 - 8/6) - 9/4 = -11/6 - 9/4 = -22/12 - 27/12
= -49/12
a + ( b + c) = -1/2 + (-4/3 - 9/4) = -1/2 + (-16/12 - 27/12) = -1/2 - 43/12
= -6/12 - 43/12 = -49/12